2021
DOI: 10.3389/fphys.2021.723690
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Nicotinamide Adenine Dinucleotide Biosynthesis in the Kidney of Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is a global public health problem with high morbidity and mortality. Decreased nicotinamide adenine dinucleotide (NAD+) levels were found to be associated with aging, cancer, and neurodegenerative and metabolic disorders. However, the alteration of renal NAD+ levels and biosynthesis pathways in CKD is less known. In the present study, we aimed to evaluate renal NAD+ levels and tested the expression of key enzymes in three NAD+ biosynthesis pathways in two different types of CKD rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…NAD+/NADH imbalance in DKD manifests as NAD+ decline and NADH overload, which aggravates oxidative stress mediated by ROC in the kidneys and causes mitochondrial dysfunction, energy metabolic disorders and inactivation of various NAD+-dependent enzymes [ 51 ]. In a study, impaired NAD+ synthesis in mice with CKD was associated with decreased expression of key enzymes, including quinolinate phosphoribosyl transferase (QPRT) in the NAD+ de novo synthesis pathway and nicotinamide nucleotide adenylyl transferase 1 (NMNAT1) and NMNAT 3 in the salvage synthesis pathway [ 54 ]. In this study, the expression of NAMN (precursor to the NAD+ de novo synthesis pathway) and niacinamide (NAM, precursor to the salvage synthesis pathway) was increased after EMPA treatment, indicating that these key enzymes may act as targets for EMPA to amend energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…NAD+/NADH imbalance in DKD manifests as NAD+ decline and NADH overload, which aggravates oxidative stress mediated by ROC in the kidneys and causes mitochondrial dysfunction, energy metabolic disorders and inactivation of various NAD+-dependent enzymes [ 51 ]. In a study, impaired NAD+ synthesis in mice with CKD was associated with decreased expression of key enzymes, including quinolinate phosphoribosyl transferase (QPRT) in the NAD+ de novo synthesis pathway and nicotinamide nucleotide adenylyl transferase 1 (NMNAT1) and NMNAT 3 in the salvage synthesis pathway [ 54 ]. In this study, the expression of NAMN (precursor to the NAD+ de novo synthesis pathway) and niacinamide (NAM, precursor to the salvage synthesis pathway) was increased after EMPA treatment, indicating that these key enzymes may act as targets for EMPA to amend energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Since improvement in renal fibrosis can also be seen through further SIRT6 overexpression, we thought it might be a compensatory mechanism. Besides, the level of NAD was declined in the development of CKD, which might also contributed to the defective function of SIRT6 ( Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…NAD + metabolism is considered a therapeutic target for kidney disease. 35 , 36 , 56 , 57 Recently, Faivre et al found that impaired NAD + biosynthesis exacerbated acute kidney injury. 36 Our results showed that metabolites related to mitochondrial function changed, such as NAD and taurine, which were well-known antioxidant substrates.…”
Section: Discussionmentioning
confidence: 99%